2017
DOI: 10.1038/s41467-017-02094-y
|View full text |Cite
|
Sign up to set email alerts
|

ORAI channels are critical for receptor-mediated endocytosis of albumin

Abstract: Impaired albumin reabsorption by proximal tubular epithelial cells (PTECs) has been highlighted in diabetic nephropathy (DN), but little is known about the underlying molecular mechanisms. Here we find that ORAI1-3, are preferentially expressed in PTECs and downregulated in patients with DN. Hyperglycemia or blockade of insulin signaling reduces the expression of ORAI1-3. Inhibition of ORAI channels by BTP2 and diethylstilbestrol or silencing of ORAI expression impairs albumin uptake. Transgenic mice expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…To identify the pathway of Ca 2+ influx activated by subsequent application of 2.5 mM extracellular Ca 2+ after store depletion, we investigated the effects of CRAC channel inhibitors, synta66 ( Beech, 2012 ; Kruchten et al, 2012 ; Derler et al, 2013 ; Molnár et al, 2016 ) and BTP2 ( Ishikawa et al, 2003 ; Zitt et al, 2004 ; Zeng et al, 2017 ), on the Ca 2+ influx. After store depletion by pretreatment of 10 μM TG in the absence of extracellular Ca 2+ , application of 2.5 mM extracellular Ca 2+ increased [Ca 2+ ] i to a peak value of 1.32 ± 0.04 F / F 0 units ( N = 9).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the pathway of Ca 2+ influx activated by subsequent application of 2.5 mM extracellular Ca 2+ after store depletion, we investigated the effects of CRAC channel inhibitors, synta66 ( Beech, 2012 ; Kruchten et al, 2012 ; Derler et al, 2013 ; Molnár et al, 2016 ) and BTP2 ( Ishikawa et al, 2003 ; Zitt et al, 2004 ; Zeng et al, 2017 ), on the Ca 2+ influx. After store depletion by pretreatment of 10 μM TG in the absence of extracellular Ca 2+ , application of 2.5 mM extracellular Ca 2+ increased [Ca 2+ ] i to a peak value of 1.32 ± 0.04 F / F 0 units ( N = 9).…”
Section: Resultsmentioning
confidence: 99%
“…These localized ER structures also express early endosome markers such as Rab5 and EEA1 43 , but are not recognized by the N-terminal STIM1 antibod-ies; therefore, these domains likely contain the alt1-Stim1A splice combination. Whether a permanent association with these Stim1 variants and Orai in the PM is required for endocytosis and is related to the finding that Orai channels are critical for receptor-mediated endocytosis of albumin in also in proximal tubular epithelial cells 44 requires further investigation and generation of splice-specific knock-out models. What also remains unclear is how the dramatic remodeling and various assemblies at these specializations are kept in a dynamic equilibrium and how they are regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Orai1 tagged with a fluorescent protein such as GFP has been overexpressed have shown that Orai1 is principally located at or near the PM [1,11,12,16]. However, the results of several other studies provide evidence for the internalisation of Orai1 to endosomes, cycling and trafficking of Orai1 between the PM and intracellular organelles, and the location of Orai in acidic organelles including secretory granules [43][44][45][62][63][64][65][66]. It is also interesting to note that the distribution of Orai1 amongst the liver subcellular fractions is quite different from that of TRPM2.…”
Section: Discussionmentioning
confidence: 99%